Complicity Among Female Perpetrators of Crimes, with Special Reference to Cases from the Republic of North Macedonia - Maksimova, Elena; Koshevaliska, Olga; Naneva, Ivona (NBP. Nauka, bezbednosti, policija, 2023)
Historical teachings and attempts to understand female's overall participation in criminality have shown us that at certain moments the idea that science had about women's participation is reduced to her inciting or helping in the commission of criminality. Namely, it is considered that the "chivalrous" behaviour of the man contributed to less and less frequent detection of the criminal behaviour of the woman. One of the characteristics that prevails in the majority of cases when a woman appears as a perpetrator of a crime, is that she does not do it alone. In women, the affect prevails and she is independent in the role of a criminal when it is done in affection, especially when committing murders or serious physical injuries to an intimate partner or a close person, but when she seriously engages in criminal, recidivist and professional activities, she is usually accompanied by other persons, so it occurs as a co-perpetrator or as an accomplice in the crime, We think that this topic is interesting to consider for reasons that the overall statistics might be very different in relation to the total participation of women in criminality if they are left alone at any moment, and also depending on who appears in the role of a co-perpetrator. Through an analysis of the theoretical understanding of the problem and statistics in our country, we want to check whether such understandings are correct and whether we could contribute
Keywords: woman, perpetrator, co-perpetrator, crime, accomplice, North Macedonia